2017
DOI: 10.1523/jneurosci.1230-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Tau Strains from Human Brains Recapitulate the Diversity of Tauopathies in Nontransgenic Mouse Brain

Abstract: Pathological tau aggregates occur in Alzheimer's disease (AD) and other neurodegenerative tauopathies. It is not clearly understood why tauopathies vary greatly in the neuroanatomical and histopathological patterns of tau aggregation, which contribute to clinical heterogeneity in these disorders. Recent studies have shown that tau aggregates may form distinct structural conformations, known as tau strains. Here, we developed a novel model to test the hypothesis that cell-to-cell transmission of different tau s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
418
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 302 publications
(445 citation statements)
references
References 51 publications
(40 reference statements)
27
418
0
Order By: Relevance
“…Seeding of human tau from homogenates of AD and tauopathies with neuronal and glial components is also observed after inoculation into the brain of wild-type mice [178,179].…”
Section: Disease Progression: Seeding and Spreading; Role Of Astrocytesmentioning
confidence: 93%
See 1 more Smart Citation
“…Seeding of human tau from homogenates of AD and tauopathies with neuronal and glial components is also observed after inoculation into the brain of wild-type mice [178,179].…”
Section: Disease Progression: Seeding and Spreading; Role Of Astrocytesmentioning
confidence: 93%
“…Seeding and spreading of abnormal tau occurs after inoculation of brain homogenates from AD and other tauopathies into the brain of transgenic mice over-expressing human tau or mutated tau [163,[173][174][175]. The type of deposits in the inoculated animals seems to be disease-dependent in the few tauopathies so far studied, which suggests the occurrence of different species or strains of tau depending on the disease [176][177][178]. However, these models have a natural substrate of abnormal tau production that makes it difficult to separate the propagation itself from what is induced.…”
Section: Disease Progression: Seeding and Spreading; Role Of Astrocytesmentioning
confidence: 99%
“…Wild type animals injected with tau extracts from human P301S mice resulted in Gallyas silver and AT100 positive threads and coiled bodies at the site of injection [71], but no NFTs or progression of disease were observed at 6 and 12 months post-injection. In a later study, injection of up to 8 µg of tau protein induced tau pathology, as well as spreading in non-transgenic mice [74]. Furthermore, neuropil threads and oligodendroglial coiled bodies were observed in wild type mice following injection of AD, TD or PSP brain extracts; only astroglial tau inclusions positive for AT8 or AT100 were observed post injection of CBD brain extracts [70].…”
Section: Experimental Seeding Of Tau Protein Lead To Progression Of Pmentioning
confidence: 85%
“…Moreover, in most of these cases tau pathology in the form of NFTs, NTs and argyrophilic grains were observed. On the contrary, few studies only demonstrated presence of hyper phosphorylated tau inclusions after seeding of tau from human AD without formation of NFTs [27,72,74,106]. In these studies, spreading of tau pathology from site of injection was observed.…”
Section: The Role Of Misfolded Tau In the Seeding And Propagationmentioning
confidence: 93%
See 1 more Smart Citation